Student Finance and the Islamic Prohibition on Interest-Based Loans: Does the UK Have a Legal Obligation to Offer Muslim University Students an Alternative Student Loan Scheme Which Aligns with Islamic Law? - Al - Astewani, Amin; Sallam, Ahmed (Invest Journal of Sharia & Economic Law, 2025)
Access to higher education in the United Kingdom is governed by a comprehensive legal framework that upholds equality and prohibits discrimination under domestic and international law. Nevertheless, the current student finance system poses significant challenges for adherents of Islam due to the Islamic prohibition on usury, which is inherent in the interest charged on conventional student loans. This financial exclusion extends beyond matters of religious accommodation, as it directly implicates the fundamental right to education and the principle of equality. This study explores whether the UK government has a legal obligation to provide adequate alternative student loan schemes aligned with Islamic principles to ensure equitable access to higher education. It critically examines the UK’s obligations under international human rights law and domestic legislation, focusing on the right to education and the principles of equality and non-discrimination.